Influence of Enhanced Recovery Pathway on Surgical Site Infection after Colonic Surgery - Caroline Gronnier; Fabian Grass; Christiane Petignat; Basile Pache; Dieter Hahnloser; Giorgio Zanetti; Nicolas Demartines; Martin Hübner (Gastroenterology Research and Practice)
Background. The present study aimed to evaluate a potential effect of ERAS on surgical site infections (SSI). Methods. Colonic surgical patients operated between May 2011 and September 2015 constituted the cohort for this retrospective analysis. Over 100 items related to demographics, surgical details, compliance, and outcome were retrieved from a prospectively maintained database. SSI were traced by an independent National surveillance program. Risk factors for SSI were identified by univariate and multinomial logistic regression. Results. Fifty-four out of 397 patients (14%) developed SSI. Independent risk factors for SSI were emergency surgery (OR 1.56; 95% CI 1.09–1.78, p=0.026), previous abdominal surgery (OR 1.7; 95% CI 1.32–1.87, p=0.004), smoking (OR 1.71; 95% CI 1.22–1.89, p=0.014), and oral bowel preparation (OR 1.86; 95% CI 1.34–1.97, p=0.013), while minimally invasive surgery (OR 0.3; 95% CI 0.16–0.56, p<0.001) protected against SSI. Compliance to ERAS items of >70% was not retained as a protective factor for SSI after multivariate analysis (OR 0.94; 95% CI 0.46–1.92, p=0.86). Conclusions. Smoking, open and emergency surgery, and bowel preparation were risk factors for SSI. ERAS pathway had no independent impact while minimally invasive approach did. This study was registered under ResearchRegistry.com (UIN researchregistry2614).